IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 6 TAHUN 2003 DALAM RANGKA PENANGANAN ANAK JALANAN DI DINAS SOSIAL KOTA MEDAN - Lase, Masbin Setia; Panjaitan, Maringan; Lumbanraja, Riana (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
This study aims to determine the obstacles or challenges in the implementation of policies for dealing with street children in the Medan City Social Service. Street children are a social problem that has become a trend of life in big cities in Indonesia, including the city of Medan. In the context of handling street children, the Medan city government, in this case the Medan City Social Service, has implemented handling programs based on Regional Regulation Number 6 of 2003 concerning the Prohibition of Homeless and Begging and Immoral Practices in Medan City. The handling programs that have been carried out so far are considered to be effective and relevant to the existing problems, but even so, it turns out that street children are still found at certain points in the city of Medan, for example at Simpang Pos Padang Bulan. The type of research conducted in this research is qualitative research. Where this research goes into the field that has become the object of research to obtain data sources, such as conducting interviews with informants directly and also making direct observations. The results of this study indicate that there are obstacles in the implementation of policies for handling street children in the city of Medan which causes street children to still exist in the city of Medan even though handling programs have been implemented.